Characterizing the Neuroimaging and Histopathological Correlates of Cerebral Small Vessel Disease in Spontaneously Hypertensive Stroke-Prone Rats - Hannawi, Yousef; Caceres, Eder; Ewees, Mohamed G.; Powell, Kimerly A.; Bratasz, Anna; Schwab, Jan M.; Rink, Cameron L.; Zweier, Jay L. (Frontiers in Neurology, 2021)
Introduction: Spontaneously Hypertensive Stroke-Prone Rats (SHRSP) are used to model clinically relevant aspects of human cerebral small vessel disease (CSVD). To decipher and understand the underlying disease dynamics, assessment of the temporal progression of CSVD histopathological and neuroimaging correlates is essential. Materials and Methods: Eighty male age-matched SHRSP and control Wistar Kyoto rats (WKY) were randomly divided into four groups that were aged until 7, 16, 24, and 32 weeks. Sensorimotor testing was performed weekly. Brain MRI was acquired at each study time point followed by histological analyses of the brain. Results: Compared to WKY controls, SHRSP showed significantly higher prevalence of small subcortical hyperintensities on T2w imaging that progressed in size and frequency with aging. Volumetric analysis revealed smaller intracranial and white matter volumes on brain MRI in SHRSP compared to age-matched WKY. Diffusion Tensor Imaging (DTI) showed significantly higher mean diffusivity in the corpus callosum and external capsule in WKY compared to SHRSP. SHRSP displayed signs of motor restlessness compared to WKY represented by hyperactivity in sensorimotor testing at the beginning of the experiment which decreased with age. Distinct pathological hallmarks of CSVD such as enlarged perivascular spaces, microbleeds/red blood cell extravasation, hemosiderin deposits and lipohyalinosis/vascular wall thickening progressively accumulated with age in SHRSP. Conclusions: Four stages of CSVD severity in SHRSP are described at the study time points. In addition, we find that quantitative analyses of brain MRI enable identification of in vivo markers of CSVD that can serve as endpoints for interventional testing in therapeutic studies.